Unveiling a potential threat to forest ecosystems: molecular diagnosis of Alliaria petiolata, a newly introduced alien plant in Korea - Choi, Tae-Young; Son, Dong Chan; Oh, Ami; Lee, Soo-Rang (Frontiers in Plant Science, 2024)
Identifying stages of a species invasion in a new habitat (i.e., colonization, establishment, and landscape spread) and their primary determinants in biological invasion warrants attention, as it provides vital insights for preventing non-native species from becoming pervasive invaders. However, delineating invasion stages and their associated factors can pose significant challenges due to the ambiguous distinctions between these stages. Alliaria petiolata, one of the most noxious weeds in woodland habitats, has recently been introduced to Korea and observed in a few distant locations. Although the plant’s spread has been relatively slow thus far, rapid spread is highly likely in the future, given the high invasive potential reported elsewhere. We indirectly diagnose the current status of A. petiolata invasion in Korea through the assessment of genetic diversity and phylogenetic inferences using genome-wide molecular markers and cytological data. We analyzed 86 individual samples collected from two native and six introduced populations, employing 1,172 SNPs. Our analysis estimated within- and among-population genetic diversity and included two clustering analyses. Furthermore, we investigated potential gene flow and reticulation events among the sampled populations. Our data unraveled that Korean garlic mustard exhibits a hexaploid ploidy level with two distinct chromosome numbers, 2n = 36 and 42. The extent of genetic diversity measured in Korean populations was comparable to that of native populations. Using genome-wide SNP data, we identified three distinct clusters with minor gene flow, while failing to detect indications of reticulation among Korean populations. Based on the multifaceted analyses, our study provides valuable insights into the colonization process and stressed the importance of closely monitoring A. petiolata populations in Korea.